Re-examining the characteristics of pediatric multiple sclerosis in the era of antibody-associated demyelinating syndromes. (November 2022) - Yılmaz, Ünsal; Gücüyener, Kıvılcım; Yavuz, Merve; Öncel, İbrahim; Canpolat, Mehmet; Saltık, Sema; Ünver, Olcay; Çıtak Kurt, Ayşegül Neşe; Tosun, Ayşe; Yılmaz, Sanem; Özgör, Bilge; Erol, İlknur; et al.
Abstract: Background: The discovery of anti-myelin oligodendrocyte glycoprotein (MOG)-IgG and anti-aquaporin 4 (AQP4)-IgG and the observation on certain patients previously diagnosed with multiple sclerosis (MS) actually have an antibody-mediated disease mandated re-evaluation of pediatric MS series. Aim: To describe the characteristics of recent pediatric MS cases by age groups and compare with the cohort established before 2015. Method: Data of pediatric MS patients diagnosed between 2015 and 2021 were collected from 44 pediatric neurology centers across Türkiye. Clinical and paraclinical features were compared between patients with disease onset before 12 years (earlier onset) and ≥12 years (later onset) as well as between our current (2015–2021) and previous (<2015) cohorts. Results: A total of 634 children (456 girls) were enrolled, 89 (14%) were of earlier onset. The earlier-onset group had lower female/male ratio, more frequent initial diagnosis of acute disseminated encephalomyelitis (ADEM), more frequent brainstem symptoms, longer interval between the first two attacks, less frequent spinal cord involvement on magnetic resonance imaging (MRI), and lower prevalence of cerebrospinal fluid (CSF)-restricted oligoclonal bands (OCBs). The earlier-onset group was less likely to respond to initial disease-modifying treatments. Compared to our previous cohort, the current series had fewer patients with onset <12 years, initial presentation with ADEM-like features, brainstem or cerebellar symptoms, seizures, and spinal lesions on MRI. The female/male ratio, the frequency of sensorial symptoms, and CSF-restricted OCBs were higher than reported in our previous cohort. Conclusion: Pediatric MS starting before 12 years was less common than reported previously, likely due to exclusion of patients with antibody-mediated diseases. The results underline the importance of antibody testing and indicate pediatric MS may be a more homogeneous disorder and more similar to adult-onset MS than previously thought. Highlights: The incidence of pediatric MS is estimated as 0.68 per 100, 000 children in Turkey. Careful exclusion of MOG-IgG disease and other MS mimics allowed accurate description of pediatric MS in this series. No cases of primary progressive MS were recorded among the 634 pediatric MS patients. Onset before 12 years and ADEM-like presentation were less frequent than previously reported. Pediatric MS appears more homogeneous and more similar to adult-onset MS than previously thought.